Characteristics of a Subject in Economic Crime Committed Through Abuse of Official Position - E. A. Tyuleeva; A. A. Kuznetsov (Сибирское юридическое обозрение, 2015)
The article considers the content of the aggravating circumstance of a number of crimes in the sphere of economics, that is, abusing of official position. The authors come to the conclusion that this attribute includes not only usage of official powers but also usage of power authority, position, official relations, and influence of administrative staff.